Analisis Efektivitas dan Kontribusi Pajak Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) Terhadap Pendapatan Asli Daerah - Muh Fachrul Firdaus; Nur Afiah; Masdar Ryketeng (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
This study aims to analyze the effectiveness and contribution of the Land and Building Rights Acquisition Tax (BPHTB) to the Locally-Generated Revenue (PAD) of Barru Regency. The data collection technique used is documentation. This study employs a quantitative method with an analysis of the effectiveness ratio and contribution ratio. This study uses primary data which includes regional tax revenue reports for the 2021-2023 period. The results indicate that the collection effectiveness of the Land and Building Rights Acquisition Tax (BPHTB) in Barru Regency during 2021-2023 is still considered effective, with an average effectiveness rate of 92.98%. However, the contribution of BPHTB to Locally-Generated Revenue (PAD) remains very low with an average rate 3,36%.